Spontaneous Bladder Rupture and Pelvic Fracture Due To Bladder Cancer - ORAY, Deniz (Turk J Emerg Med, 2016)
Bladder rupture is a rare complication following bladder cancer, but has a high mortality rate. Since bladder rupture is an emergency, the diagnosis and treatment of the cancer is usually delayed. Here we report a 56-year-old male patient who presented to our emergency department with severe abdominal pain, abdominal distension, left leg pain and difficulty in walking without history of significant trauma and ended up with diagnoses of spontaneous bladder rupture and non-traumatic pelvic fracture caused by bladder carcinoma.